Friction reduction by nanometal additives to mineral oil; Tribologia : tarcie, zuzycie, smarowanie; № 6 - Tarasov S. Yu. Sergei Yulievich (2002, 2002)
Friction and wear tests of metal nanopowder additives to mineral oil for lubricating steel-steel pair have been carried out. The copper, zinc and brass nanopowders have been produced by electric explosion of metallic wires. In spite of absence of selective transfer wear mode, it was noted the reduction in friction and wear especially at high sliding speed and load. World tribology practice shows that metal-containing additives to the lubricants might enhance both life and reliability of machine parts. Most of all this refers to formation of thin antiwear films of the rubbing surfaces, Soft films formed from chemical elements of the additive formulation are easy to deform under contact load and thus reduce the tangent stresses in the base material, which in turn enhances friction and wear characteristics of a unit. However, it could happen that no such anti-wear films are formed during friction but both friction and wear are reduced. Furthermore, such an additive contributes to reducing adhesion between contacting bodies by modifying transfer layer formed between them. Another aspect is that deformation in friction occurs at different scale levels and it was shown [L. 1] that a crossover from normal oxidation wear to catastrophic (adhesion and seizure) is characterized by a sharp growth in the size of structural units involved in wear. In connection with this, modification of wear surfaces as well as transfer layer to keep the number of adhesion bonds below its critical value is also very important. We have studied effect of metallic nanopowdcr additives (copper, brass and zinc) made by electric explosion of wires to mineral oil on friction and wear of steel-to-steel friction couples in a wide range of loads and friction speeds.